Treatment for woolscouring effluent through bioacidification by acidithiobacillus thiooxidans. (24th February 2010) - He, Feng; Zhou, Lixiang
In this study, a promising process called bioacidification was used to remove organic pollutant from Woolscouring Effluent (WSE) by emulsion destabilisation. Chemostat experiments of bioacidification treatment inoculated with Acidithiobacillus thiooxidans were operated at high wastewater recycle ratios to achieve shorter Hydraulic Retention Time (HRT). Results exhibited high COD removal efficiency and gradual decrease in treatment time, and the recycle ratio of 4 was determined as the optimal choice due to the maximal treatment efficiency. After treatment with 36 h HRT, 42.6 g L−1 COD (roughly 92% of total COD) was removed, suggesting that this process could be applied in full scale and incorporated into an overall treatment package.